Itch Processing in the Skin - Schmelz, Martin (Frontiers in Medicine, 2019)
Itch can result from activity of specialized primary afferent neurons (“pruriceptors”) that have been shown to express certain molecular markers such as B-type natriuretic peptide and several members of the Mrgpr-family in rodents. On the other hand, neurons involved in pain processing (“nociceptors”) can also provoke itch when the activation site is restricted to an isolated tiny spot within the epidermis. Individuals classified as having sensitive skin report increased itch and pain sensations upon weak external stimuli that are not painful or itchy in the control group. Numerous possible factors could contribute to sensitive skin along the pathway of transduction of the external stimuli into peripheral neuronal signals followed by neuronal processing finally resulting in the perception: a) reduced local protective factors leading to impaired skin barrier function, b) increased production of excitatory skin mediators, c) sensitized peripheral neurons, d) facilitated spinal and central processing and e) reduced descending inhibition from the central nervous system. For all of those pathophysiological mechanisms there are clinical examples such as atopic dermatitis (a,b,c), neuropathic itch (c,e), and restless leg syndrome (d,e). However, none of these factors have been directly linked to the occurrence of sensitive skin. Moreover, individuals reporting sensitive skin are heterogeneous and subpopulations with defined pathophysiology have not yet been identified. Given that the condition is reported by about 50% of women and thereby includes many healthy individuals it appears problematic to assign a definitive pathophysiological mechanism to it.